The Evaluation of Compliance of the Cerrahpaşa School of Medicine Education Program with the National Core Education Program - Çakmakkaya, Özlem Serpil; Yaman, Muhittin Onur; Ar, Muhlis Cem (Cerrahpaşa Medical Journal, 2020)
Objective: Outcome-based education approaches, which have gained priority in medical education, assessment of competencies of graduates, and the development of a national core curriculum have all influenced the program evaluation and development at the Cerrahpaşa School of Medicine, and comprehensive improvement studies have been conducted over the last two decades. As a part of the latest stage of these studies, we aimed to systematically analyze the compliance level of the Cerrahpaşa School of Medicine education program curriculum with the National Core Education Program (NCEP-UÇEP: Ulusal Çekirdek Eğitim Programı) published in 2014. Methods: The compliance of the Cerrahpaşa School of Medicine education program curriculum with the “Symptoms/Conditions” and “Core Diseases and Clinical Problems” lists of the NCEP was evaluated in five stages: creation of a database, preliminary studies to evaluate the suitability of the database, training workshops, data entry, and creation of the main database. Results: Results showed that the Cerrahpaşa School of Medicine education program curriculum covers all the titles included in the “Symptoms/Conditions” and “Core Diseases and Clinical Problems” lists of the NCEP. The Basic Medical Sciences, Internal Sciences, and Surgical Sciences programs cover 38%, 97%, and 72%, respectively, of the “Core Diseases and Clinical Problems” list of the NCEP. The “Symptoms/Conditions” checklist is covered in 17%, 97%, and 68% of the Basic Medical Sciences, Internal Sciences, and Surgical Sciences programs, respectively. Conclusion: The Cerrahpaşa School of Medicine training program was found to be compliant with NCEP 2014, and it covered all the titles included in the NCEP. The systematic analysis provided data for improvement of the training program and strengthening of its level of integration. Cite this article as: Çakmakkaya ÖS, Yaman MO, Ar MC. The Evaluation of Compliance of the Cerrahpaşa School of Medicine Education Program with the National Core Education Program. Cerrahpasa Med J 2020; 44(1): 41-50.